Hypothesis testing in forestry, agriculture and ecology: Use and overuse of the 0.05 and 0.01 significance levels - Antúnez, Pablo; Rubio-Camacho, Ernesto Alonso; Kleinn, Christoph (Ecosistemas y Recursos Agropecuarios, 2021)
Hypothesis testing in forestry, agriculture and ecology: Use and overuse of the 0.05 and 0.01 significance levels